2009
DOI: 10.2147/oarrr.s5508
|View full text |Cite
|
Sign up to set email alerts
|

A suppressive effect of prostaglandin E2 on the expression of SERPINE1/plasminogen activator inhibitor-1 in human articular chondrocytes: An in vitro pilot study

Abstract: Prostaglandin E2 (PGE2) is expressed in articular joints with inflammatory arthropathy and may exert catabolic effects leading to cartilage degradation. As we observed in a preliminary experiment that PGE2 suppressed the expression of SERPINE1/plasminogen activator inhibitor (PAI)-1 mRNA in chondrocytes, we focused on the effect of PGE2 on PAI-1 in a panel of cultured chondrocytes obtained from osteoarthritic patients. Specifically, articular cartilage specimens were obtained from patients with osteoarthritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Interestingly, studies have shown that there is a cross talk between plasminogen activation system and PGE2 synthesis/function (47)(48)(49). It has been reported that PGE2 suppresses PAI-1 expression in human articular chondrocytes (48) It has also been demonstrated that the antifibrotic effects of plasmin occur via PGE2 synthesis in human and mice (47), whereas serpine1 (PAI-1) disrupts PGE2 production (49). Whether increased PAI-1 in IPF and/or aged mouse lung results from decreased PGE2 or whether PAI-1 divergently regulates the sensitivity of fibroblast and ATII cells to apoptosis through suppressing PGE2 synthesis in these cells warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies have shown that there is a cross talk between plasminogen activation system and PGE2 synthesis/function (47)(48)(49). It has been reported that PGE2 suppresses PAI-1 expression in human articular chondrocytes (48) It has also been demonstrated that the antifibrotic effects of plasmin occur via PGE2 synthesis in human and mice (47), whereas serpine1 (PAI-1) disrupts PGE2 production (49). Whether increased PAI-1 in IPF and/or aged mouse lung results from decreased PGE2 or whether PAI-1 divergently regulates the sensitivity of fibroblast and ATII cells to apoptosis through suppressing PGE2 synthesis in these cells warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%